Manganese determination by GFAAS in feces and fish feed slurries - Loureiro, Vanessa Rosa [UNESP]; Saleh, Mayra A. D. [UNESP]; Moraes, Paula M. [UNESP]; Neves, Renato C. F. [UNESP]; Silva, Fabio A. [UNESP]; Padilha, Cilene C. F. [UNESP]; Padilha, Pedro de Magalhães [UNESP] (FapUNIFESP (SciELO), 2007)
This paper presents a simple, fast and sensitive method to determine manganese in samples of feces and fish feed by graphite furnace atomic absorption spectrometry (GFAAS) by the direct introduction of slurries into the graphite tube. The limits of detection (LOD) and quantification (LOQ) calculated for 20 readings of the blank of the standard slurries (0.50 % m/v of feces or feed devoid of manganese) were 28 and 92 μg kg-1 for the standard feces slurries and 34 and 110 μg kg-1 for the standard feed slurries. The proposed method was applied in bioavailability studies of manganese in different fish feeds and their results proved compatible with those obtained for samples mineralized by acid digestion using microwave oven. ©2007 Sociedade Brasileira de Química.
Keywords: Chemical modifier; GFAAS; Manganese determination; Slurries samples